The Effectiveness of Career Counselling Model towards Career Maturity and Self-Concept Level of Former Drug Addicts - Amin Al Haadi Bin Shafie; Che Syaza Syamimi Binti Che Jamri; Mohd Nurul Hadi Bin Yatau; Mohd Khairul Anuar Bin Rahimi; Nurhafizah Binti Mohd Sukor; Chong Siew Ngoh; Hishamuddin Abdul Wahab; Siti Nubailah Mohd Yusof (Human Resource Management Academic Research Society, 2024)
Indexed by ERA